Effectiveness and Renal Safety of Tenofovir Alafenamide Fumarate among Chronic Hepatitis B Patients: Real‐World Study. Issue 6 (1st April 2021) - Farag, Mina S.; Fung, Scott; Tam, Edward; Doucette, Karen; Wong, Alexander; Ramji, Alnoor; Conway, Brian; Cooper, Curtis; Tsoi, Keith; Wong, Philip; Sebastiani, Giada; Brahmania, Mayur; et al.
Abstract: Tenofovir alafenamide fumarate (TAF) has high plasma stability resulting in fewer renal adverse events compared to tenofovir disoproxil fumarate (TDF) in chronic hepatitis B (CHB) patients. We aimed to study the effectiveness and renal safety of TAF in a real‐world setting, in patients with or without compromised kidney function. CHB patients (Nucleos(t)ide Analogue [NA]‐naïve or experienced) who received TAF >1 year from 11 academic institutions as part of the Canadian Hepatitis B Network (CanHepB) were included. Kidney function was measured by estimated glomerular filtration rate (eGFR) as per Cockcroft‐Gault. Patients were followed for up to 160 weeks. Of 176 patients receiving TAF, 143 switched from NA (88% TDF), and 33(19%) were NA naïve. Majority of NA‐naïve patients (75%) achieved undetectable HBV DNA after one year of TAF treatment. Majority of patients with eGFR <60 mL/min who had renal deterioration during TDF (76%) reversed to eGFR increase after one year of TAF ( p =0.009). Among patients with stage 2 chronic kidney disease (CKD) (eGFR 60–89), the estimated eGFR decline during TDF was halted after switching to TAF ( p =0.09). NA‐experienced patients with abnormal ALT before TAF showed a significant decline after switching to TAF: −0.005 [−0.006 – −0.004] log10 ULN U/L/month, p <0.001). In CHB patients, TAF was safe, well‐tolerated and effective in this real‐world cohort. Switching to TAF led to improved kidney function, particularly in those with stage 2 CKD, which suggests that the indication for TAF in the guidelines could be extended to patients with an eGFR higher than 60 mL/min.